Odpowiedzi

2010-04-06T15:02:08+02:00

1) = sprzeczenie
3(3 - 5y) = 90 - 5 (3y -2 )
9-15y=90-15y+10
no i sprzeczność - 2 razy pojawia się -15y

2) z= 8
1/4 z + (z - 6) = 2/3 (z - 2)
2+2=4
4=4
2010-04-06T15:04:56+02:00
1)
3(3 - 5y) = 90 - 5 (3y -2 )
9-15y = 90-15y+10
-15y+15y = 90+10-9
0 = 91

2) z= 8
1/4 z + (z - 6) = 2/3 (z - 2)
1/4*8+(8-6) = 2/3(8-2)
2+2 = 4
4 = 4
2010-04-06T15:18:50+02:00
1)
9 - 15y = 90 - 15y +10
-15y+15y=90 +10 - 9
0y = 91 ; równanie sprzeczne

2)1/4 *8 +(8-6)= 2/3 (8 - 2)
2 + 2 = 2/3 * 6
4 = 4